Chemotherapy Related Optic Neuritis - AS, Nur; CH, Jemaima; Ismail, Fuad; MK, Safinaz (IIUM Medical Journal Malaysia, 2017)
In children, most cases of optic neuritis are immune-related. Less frequently, it may also be due to demyelinating disorders. Other secondary causes such as infection of adjacent structures or infiltration are even rarer. The occurrence of optic neuritis in children on chemotherapy also has not being extensively reported. We report a case of bilateral optic neuritis in a young girl with subacute visual loss after receiving systemic chemotherapy for embryonal ovarian carcinoma.